Conservative accounting and equity valuation - Zhang, Xiao-Jun (Journal of Accounting and Economics, 2000)
This paper examines how conservative accounting affects the relation between accounting data and firm value. The analysis shows that conservative accounting can be characterized equivalently in terms of book value, earnings, or book rate of return. Furthermore, capitalized earnings generally provide a less biased estimate of equity value than book value does. In addition, firm growth affects the way earnings and book value are combined in valuation. A weighted average of book value and capitalized earnings, with the weight on earnings being an increasing and convex function of growth, yields an asymptotically unbiased estimate of equity value. When growth is positive, the weight on book value is negative.